1986
DOI: 10.1111/j.1365-2559.1986.tb02472.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of basement membrane antigens in the histopathological evaluation of laryngeal dysplasia and neoplasia

Abstract: Immunocytochemical detection of intrinsic components of the basement membrane (type IV collagen and laminin) was performed in biopsies of carcinoma in situ, dysplasia and hyperplasia of the laryngeal mucosa. We found a distinct and continuous basement membrane, containing both laminin and type IV collagen, at the border between epithelial cells and mesenchymal stroma in normal as well as in hyperplastic and dysplastic mucosa. In contrast, irregular discontinuities were found in some cases of carcinoma in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…Conversely, almost all patients with CIV pattern II staining died by two years: 8 the first year with distant (5) or regional (2) metastasis or both (1); three more patients died the second At three years of evolution, the difference in survival as related to the CIV staining pattern was still highly significant (P<0.001) (Table II). For this statistical analysis, we used the Armitage-Cochran test (Table II) (Ingber et al, 1981), breast (Albrechtsen et al, 1981;Siegal et al, 1981), colon (Burtin et al, 1982;Forster et al, 1984), brain (McArdle et al, 1984), thyroid gland (Miettinen & Virtanen, 1984), melanomas (Natali et al, 1985) and laryngeal specimens (Visser et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, almost all patients with CIV pattern II staining died by two years: 8 the first year with distant (5) or regional (2) metastasis or both (1); three more patients died the second At three years of evolution, the difference in survival as related to the CIV staining pattern was still highly significant (P<0.001) (Table II). For this statistical analysis, we used the Armitage-Cochran test (Table II) (Ingber et al, 1981), breast (Albrechtsen et al, 1981;Siegal et al, 1981), colon (Burtin et al, 1982;Forster et al, 1984), brain (McArdle et al, 1984), thyroid gland (Miettinen & Virtanen, 1984), melanomas (Natali et al, 1985) and laryngeal specimens (Visser et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Like other epithelia, urothelium is sustained by a basement membrane which separates it from connective tissue and contains various glycoproteins of high molecular weight (Vracko, 1974;Kefalides, 1975;Orkin et al 1977). Among them, type IV collagen (CIV) forms a network which is the architectural skeleton of basement membranes and laminin plays an important role in anchoring epithelial cells to CIV Terranova et al 1980;Timpl et al 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to lack of synthesis, decreased assembly and the increase turnover or degradation/dissolution of basement membrane components during invasion supporting the concept of Bernstein et al 18 a cyclic behavior of tumor cells adhesion, synthesis and secretion of hydrolytic enzymes in degradation of basement membrane components and the extracellular matrix for cellular invasion. Furthermore Visser et al, 19 Sakr et al 13 also observed similar defects in the basement membrane component exclusively in areas adjacent to inflammatory cells. As these cells were capable of releasing enzymes which digest the basement membrane components.…”
Section: Discussionmentioning
confidence: 81%
“…Although the loss of basement membrane has not been correlated with invasive behaviour of HNSCC [40,41], but a wide variety of proteolytic enzymes and there specifi c inhibitors are reported in the development of tissue invasion and regional metastasis of HNSCC.…”
Section: Introductionmentioning
confidence: 99%